E-cigarette use and beliefs among adult smokers with substance use disorders. (June 2021) - El-Shahawy, Omar; Schatz, Daniel; Sherman, Scott; Shelley, Donna; Lee, Joshua D; Tofighi, Babak
Highlights: We estimated prevalence of e-cigarette dual use among smokers with substance use disorders. Dual e-cigarette users were more likely to have tried to quit in the past year. Overall, participants preferred to use e-cigarettes in comparison to nicotine patches/gum. E-cigarettes seem appealing to patients with substance use disorders. E-cigarette use may be effective for harm reduction among patients in addiction treatment. Abstract: Background: We explored characteristics and beliefs associated with e-cigarette use patterns among cigarette smokers requiring inpatient detoxification for opioid and/or alcohol use disorder(s). Methods: Adult cigarette smokers (≥18 years), admitted to inpatient detoxification for alcohol and/or opioid use disorder(s) in a safety-net tertiary referral center in New York City were surveyed in 2015 (n = 158). Descriptive statistics (proportions) were used to assess for demographic, clinical diagnosis, cigarette smoking patterns (exclusive and dual use of e-cigarettes). Chi-square, t -test statistics, and logistic regression models were used. Results: Among our sample of combustible cigarette users, 13.9% (n = 22) reported dual use with electronic cigarettes. Dual use did not differ by demographic or clinical variables. Compared to exclusive smokers, dual users were more likely to have tried to quit in the past year (Adjusted Odds ratio = 8.59; CI: 2.58, 28.35; p < 0.001). Dual smokers had significantly higher mean ratings perceiving that e-cigarettes can help people quit smoking compared to exclusive smokers (M = 3.7, SD= ±1.4 vs. M = 2.7, SD= ±1.5, p = 0.002) respectively . Dual users also preferred e-cigarettes over nicotine patches /gum for quitting (M = 3.7, SD= ±1.7 vs. M = 2.6, SD= ±1.6, p = 0.005) . Conclusions: E-cigarette use seems to be appealing to a small proportion of cigarette smokers with SUD. Although, dual smokers seem to use e-cigarettes for its cessation premise, they don't appear to be actively seeking to quit. E-cigarettes may offer a more effective method for harm reduction, further evaluation of incorporating it within smoking cessation protocols among patients in addiction treatment is needed.